ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI STROBERI DI KABUPATEN PURBALINGGA - Damar Jati; Zumaeroh Zumaeroh; Heri Setiawan; Andhi Johan Suzana; Marhabarani Nurjanah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Income is an important factor in a business activity. With a high income, the economic needs will be met properly. However, the difference in income in each farm is something that needs to be considered because the distribution of income is uneven. This study aims to analyze whether land area, farmer's age, education, capital, farming experience, selling price, fertilizer costs, seed costs, and labor affect the income of strawberry farmers in Serang Village, Karangreja District, Purbalingga Regency. This research includes quantitative research using a research instrument in the form of a questionnaire. The sample used is a saturated sample (census) as many as 32 farmers. The data analysis technique use multiple linear regression. The results of this study indicate that (1) land area, capital, selling price, cost of seeds have a significant positive effect on strawberry farming income in Serang Village, Karangreja District, Purbalingga Regency; (2) labor has a significant negative effect on the income of strawberry farmers in Serang Village, Karangreja District, Purbalingga Regency; (3) farmer's age, education, farming experience, and fertilizer costs have no effect on the income of strawberry farmers in Serang Village, Karangreja District, Purbalingga Regency. However, this study has limitations such as (1) it consists of several types of strawberries so it is not specific to one type of strawberry. (2) there are differences in thoughts, assumptions and opinions expressed by respondents in answering the questionnaire. So that further research is needed for further research in order to maximize the results obtained. Keywords: Income, Farming, Strawberries, Produkction